Improvement of abrasive wear resistance of the high chromium cast iron ASTM A-532 through thermal treatment cycles (2016)
High-Chromium White Cast Iron is a material highly used in mining and drilling shafts for oil extraction, due to its high wear resistance. However, because of the austenitic matrix found in the as-cast state, an adequate heat treatment cycle is necessary. This paper studies the effects of different cooling media after a destabilization treatment on the microstructure, hardening and abrasion resistance behaviors of a hypoeutectic high chromium white cast iron. The results show that although air cooling followed by immersion in CO2 can effectively reduce the retained austenite, this is not enough to transform completely the retained austenite into martensite. The low retained austenite percentages improve bulk hardness, but they decrease the abrasion resistance of the high chromium cast iron. The best combination of hardness and wear resistance was found in the samples cooled in air, due to the percentage of retained austenite and a moderate precipitation of chromium carbide.